How does artificial intelligence impact human resources performance: Evidence from a healthcare institution in the United Arab Emirates - Peigong Li; Anna Bastone; Talal Ali Mohamad; Francesco Schiavone (Journal of Innovation & Knowledge (JIK), 2023)
This study aims to explore the impact of the implementation of artificial intelligence (AI) in the healthcare sector on overall human resource (HR) practices and organizational performance. We seek to highlight the added value that adopting AI techniques in human resource management (HRM) in the healthcare sector offers to the entire ecosystem in financial and organizational terms. To tackle the research question, we conducted an explorative qualitative analysis investigating a Lebanese international healthcare center in Dubai. To obtain data triangulation, we used both primary and secondary data as a source of evidence. The study offers interesting insights into implementing AI tools in HRM across the healthcare sector and to what extent this will contribute a useful tool to gather better organizational performance. Despite the unique characteristics of the case study in the industry and country settings, this study is not without limitations. It is difficult to extend the results to the entire population. This study provides several theoretical, managerial, and policy implications that give concrete insights into how implementing AI will affect HRM processes and company performance.
Keywords: O32; M12; 650; AI; Healthcare organization; HRM; Performance measurement